Research on Childcare Support for Foreign Parents in Preschool Institutions - Taiki Fuchioka (Budapest International Research and Critics University, 2023)
Increasing number of foreign children in Japan's preschool facilities and the complexity of the problems faced by foreign families are becoming more and more apparent. The social situation of high support needs for foreign parents and the lack of necessarily adequate childcare support for foreign parents, and the existing